Incorporating ethical principles into clinical research protocols: a tool for protocol writers and ethics committees. Issue 4 (25th January 2016) - Li, Rebecca H; Wacholtz, Mary C; Barnes, Mark; Boggs, Liam; Callery-D'Amico, Susan; Davis, Amy; Digilova, Alla; Forster, David; Heffernan, Kate; Luthin, Maeve; Lynch, Holly Fernandez; McNair, Lindsay; et al.
Abstract : A novel Protocol Ethics Tool Kit ('Ethics Tool Kit') has been developed by a multi-stakeholder group of the Multi-Regional Clinical Trials Center of Brigham and Women's Hospital and Harvard. The purpose of the Ethics Tool Kit is to facilitate effective recognition, consideration and deliberation of critical ethical issues in clinical trial protocols. The Ethics Tool Kit may be used by investigators and sponsors to develop a dedicated Ethics Section within a protocol to improve the consistency and transparency between clinical trial protocols and research ethics committee reviews. It may also streamline ethics review and may facilitate and expedite the review process by anticipating the concerns of ethics committee reviewers. Specific attention was given to issues arising in multinational settings. With the use of this Tool Kit, researchers have the opportunity to address critical research ethics issues proactively, potentially speeding the time and easing the process to final protocol approval.